Isolation of Antibiotic Compound Producing Bacteria from the Soil Rhizosphere Against Escherichia Coli and Streptococcus Aureus - Rima Ernia; Yeni Indriyani; Rina SE Sitindaon; Muslimin Muslimin; Mustika Fatimah (Science Midwifery, 2021)
This research aims to isolate bacteria from the rhizosphere soil which are known to be good media for the growth of bacteria, such as Escherichia coli and Straphlococus aureus as new types of antibiotics. The method used by isolated the bacteria from rhizosphere soil of Rimpang Pacing and Guava rhizome plants and then do the cell morphology characterization, purification, propagation of antibiotic-producing bactrial isolates and continued testing the antibiotic activity of potential bacterial isolates. From the observations, it was found that the isolation of bacteria from the rhizosphere soil of the pacing rhizome had antibiotic compounds that were able to inhibit the growth of Escherichia coli and Straphlococcus aureus bacteria as indicated by the formation of a clear zone around the colony, which had an inhibitory index of 0.5 mm in Ec.2 and Bp.1 isolates is also 0.5 mm. From Both Ec.2 and Bp.1 isolates concluded that the rhizosphere soil produces an inhibitory zone that has the potential to be used as an antibiotic agent